Managing Patients with Tribocorrosion - Vinall, Maria (MD Conference Express, 2014)
The failure rate of hip replacements is an important clinical problem in adult reconstructive orthopedic surgery. Tribocorrosion in the form of articular surface material loss from metal-on-metal bearings and material loss from metal/metal modular junctions is central to the problem. This article provides an update on the clinical impact of tribocorrosion focusing on diagnostic modalities and treatment options.